A New Basal Ankylosaurid (Dinosauria: Ornithischia) from the Lower Cretaceous Jiufotang Formation of Liaoning Province, China - Han, Fenglu (Public Library of Science, 2014)
A new ankylosaurid, Chuanqilong chaoyangensis gen. et sp. nov., is described here based on a nearly complete skeleton from the Lower Cretaceous Jiufotang Formation of Baishizui Village, Lingyuan City, Liaoning Province, China. Chuanqilong chaoyangensis can be diagnosed on the basis of two autapomorphies (glenoid fossa for quadrate at same level as the dentary tooth row; distally tapering ischium with constricted midshaft) and also a unique combination of character states (slender, wedge-like lacrimal; long retroarticular process; humerus with strongly expanded proximal end; ratio of humerus to femur length  = 0.88). Although a phylogenetic analysis places Chuanqilong chaoyangensis as the sister taxon of the sympatric Liaoningosaurus near the base of the Ankylosauridae, the two taxa can be distinguished on the basis of many features, such as tooth morphology and ischial shape, which are not ontogeny-related. Chuanqilong chaoyangensis represents the fourth ankylosaurid species reported from the Cretaceous of Liaoning, China, suggesting a relatively high diversity in Cretaceous Liaoning.